Innovative Transport Systems to Promote Sustainable Mobility: Developing the Model Architecture of a Traffic Control and Supervisor System - Torrisi, Vincenza; Ignaccolo, Matteo; Inturri, Giuseppe (Computational Science and Its Applications - ICCSA 2018, 2018)
In the last decades, a big effort has been made in terms of research, strategies and initiatives to boost new forms of sustainable urban mobility, in order to reduce the externalities associated with the transport sector. While the European Commission emphasizes integrated planning at all mobility levels, on the other hand it recognizes that is equally important to make technologically modern mobility system, in order to maximize its efficiency. With regard to this technological modernization, the Intelligent Transport Systems (ITS) are considered as a tool, that to date more than any other, it allows us to manage a “smart” mobility. Based on this premise, this work concerns the development of a methodological approach to implement a traffic control and supervisor system with related infomobility services. It is identified the conceptual model that represents the basis of the system’s architecture, in order to define a set of required services, functional relationships and specific characteristics acknowledged from stakeholders’ needs, which will be involved by the system. This approach is applied to a case study in the urban area of Catania (Italy), through the implementation of a traffic monitoring, estimation and short-term forecasting system, equipped with radar sensor and a central control station for traffic data elaborations. The obtained results should concur to increase the knowledge of the actual dynamic of road traffic in urban areas, to monitor the reliability of the transport system and to obtain useful data and information that contribute to a more efficient and optimal control of mobility system.